Pertanggungjawaban Pidana Advokat Tanpa Mekanisme Pemeriksaan Kode Etik Advokat - Syaifudin, Arif; Abadi, Suwarno; Wijaya, Andy Usmina (Law and Humanity, 2023)
Advocates in carrying out their profession are under the protection of laws, statutes and codes of ethics, which cannot be prosecuted before a court, either civil or criminal, as long as they have good faith in defending the interests of their clients. However, in practice, many Advocates are caught in criminal cases in carrying out their professional duties. The purpose of this study is to analyze and find out the characteristics of good faith referred to in article 16 of Law Number 18 of 2003 concerning Advocates in terms of law enforcement and legal protection for the advocate profession and criminal liability for the actions of advocates in carrying out their professional duties without going through the mechanism of examining the Code of Ethics. . The theory used to analyze is law enforcement theory, legal protection theory, and criminal responsibility theory. The writing method used is normative writing method, by analyzing a legal issue through laws and regulations, literature, and other reference materials. The results of this study are that the work of a legal advisor is a work of trust in good faith to rectify the problems faced by clients whose existence is regulated and protected by law. The criminal responsibility of an advocate who commits a crime in carrying out his profession must be seen from the mistakes made by the advocate so that he is seen as having committed an act that meets the elements of a crime which must be proven first through an examination of the code of ethics. The government and/or legislators must pay more attention to and scrutinize the formation of statutory regulations so that there are no overlapping rules and so that one law does not conflict with another. As well as to strengthen the profession, it is hoped that there will be a need for stricter and more precise rules that can be used as a legal umbrella in professional life.